The Concurrent Validity of a Portable Ultrasound Probe for Muscle Thickness Measurements in Clinical Physiology and Functional Imaging - Homer, Kai; Cross, Matthew; Jukic, Ivan (My University, 2024)
Ultrasound imaging is extensively used by both practitioners and researchers in assessing muscle thickness (MT); however, its use in the field is constrained by the transportability of stationary devices. New portable ultrasound probes pose as a cost-effective and transportable alternative for field-based assessments. This study evaluated the concurrent validity of a portable probe (Lumify) against a laboratory-based device (Vivid S5) in measuring MT. Eighteen participants (nine males and nine females) visited the laboratory and their MT measurements were collected using each device at five different sites (anterior and posterior arm, anterior and posterior thigh, and posterior lower leg). Bland-Altman plots (systematic and proportional bias, random error, and 95% limits of agreement), Pearson's product–moment correlation coefficient (r), and paired samples t-tests with Cohen's d effect sizes (ES) were used to assess the concurrent validity of the Lumify device. Systematic bias was low at all sites ( ≤ 0.11 cm) while proportional bias was detected only at the posterior lower leg (r2 = 0.217 [r = 0.466]). The difference in MT between devices was significant only at the anterior thigh (p < 0.05); however, ES for all sites were considered trivial (ES ≤ 0.131). Linear associations were found between the devices at each site of measurement (r ≥ 0.95). These results highlight that the Lumify probe can be used interchangeably with the Vivid S5 for MT measurements, providing practitioners and researchers with a more cost-effective and portable alternative for field-based assessments.
Keywords: 1116 Medical Physiology; Physiology; 3201 Cardiovascular medicine and haematology; 3208 Medical physiology